Shorter Notices (The Muslim world, 1962)
The Structure of the Ethical Terms in the Koran. By Toshihiko Izutsu. The Religious Duties of Islam as Taught and Explained by Abu Bakr Effendi. By Mia Brandel-Syrier. E. J. Brill. Two works by Samin Khan. An Introduction to Basic Democracy. Pakistan: Ideology, Constitution, Laws, Foreign Policy. Al-Kashi on Root Extraction. By Abdul-Kader Dakhel. Middle East Economic Papers, 1961. Paul J. Klat, Editor. The Foreign Exchange Systems of Lebanon and Syria, 1939-1957. By Elias S. Saba. Transactions Vol. XVIII Edited by C. J. Mullo Weir. Telling the Good News By William MElwee Miller. Prayers of Muhammad. By A. H. Farid. The Sacred Journey. By Ahmad Kamal. Modern Muslim Koran Interpretation (1880-1960). By J. M. S. Baljon. An Elementary Classical Arabic Reader. By M. C. Lyons. Lucknow Publishing House (1861-1961). By John N. Hollister.